The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/01446193.2018.1472385
|View full text |Cite
|
Sign up to set email alerts
|

Black boxing BIM: the public client’s strategy in BIM implementation

Abstract: Building information modelling (BIM) is widely discussed in both industry and academia and studies have argued that public clients play an important role in industry's implementation of BIM. While public client initiatives have gained much interest in previous research, there is still a lack of knowledge exploring the public clients' role and choice of strategies when implementing BIM with the aim to change industry. Based on a case study of BIM implementation at the largest infrastructure client in Sweden, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…Building Information Modelling (BIM) and its influence on change and innovation in the construction industry is increasingly addressed in construction research and industry practice (Succar 2009, Linderoth 2010, Wong et al 2010, Vass and Karrbom Gustavsson 2017, Lindblad 2018). There are different definitions of BIM and one of the most commonly used definitions is provided by Succar (2009, p. 357).…”
Section: Bim As Construction Industry Game Changermentioning
confidence: 99%
See 2 more Smart Citations
“…Building Information Modelling (BIM) and its influence on change and innovation in the construction industry is increasingly addressed in construction research and industry practice (Succar 2009, Linderoth 2010, Wong et al 2010, Vass and Karrbom Gustavsson 2017, Lindblad 2018). There are different definitions of BIM and one of the most commonly used definitions is provided by Succar (2009, p. 357).…”
Section: Bim As Construction Industry Game Changermentioning
confidence: 99%
“…Through the concept of absorptive capacity (Cohen and Levinthal 1990), we explore clients' ability to recognise external BIM related knowledge, and their ability to absorb and apply this knowledge in order to drive industry change. Implications address the on-going discussion by Havenvid et al (2016) and others on clients as drivers of change and innovation, and combine that with the discussion by Linderoth (2010), Lindblad (2018), (Bosch-Sijtsema et al 2017), Vass and Karrbom Gustavsson (2017) and others on BIM as construction industry game changer.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the managerial group had the highest value of (D + R) among all groups, which means that the managerial competencies are more related to the whole competency profile of a BIM practitioner. BIM implementation influences work practices and relationships between practitioners, which demands high level managerial competencies in BIM leaders [82]. For executing BIM projects, leaders must manage two main requirements: managing the employer information requirement (EIR) and validating outcomes [83].…”
Section: Results and Findingsmentioning
confidence: 99%
“…The STA purposefully promotes the use of BIM in projects they conduct in order to drive industry adoption. However, earlier studies of the BIM initiative at the STA has indicated difficulties for clients to act as change agents when promoting BIM (Lindblad 2018) and highlighted difficulties in establishing intra-organisational acceptance for a change towards BIM (Lindblad and Karrbom Gustavsson 2017). In addition to promoting BIM, the STA has started an initiative to; more generally, promote innovation in the industry, the "Professional Client" initiative.…”
Section: Methodsmentioning
confidence: 99%